Pengembangan Sistem Operasional Downstream Logistics dengan Modifikasi P1R2 - Ariningsih, Paulina K.; Sandy, Ignatius A.; Adventia, Imanuele C. D. (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
Inaccuracy implementation of downstream logistics (DL, distribution) may decrease product quality. Quality decreament may happen due to product damange during distribution process, either duringloading-on and loading-off process, or during transportation process. Rejection product by the consumer due to quality mismatch may cause losses and non-valued added logistics activities. Integrated sistem approach for DL is proposed to minimize product damange during DL without compromising service level (SL) on the consumer. This paper describes the steps to improve DL’s operational activitiesusing management approach and modification of P1R2 algorithm (Packing First Routing Second). The final result and managerial implications of the process is formed in proposed Work Instruction (IK). The implementation of this improvement process is described using plastic furniture distribution study case of PT. X. As a result, 3 IK are produced. In addition, it is shown that proposed method can minimize non-value added logistics activities and reduce cost.